What modifies the relation between tumour size and lymph node metastases in T1 breast carcinomas?. Issue 11 (1st November 2000) - Arisio, R; Sapino, A; Cassoni, P; Accinelli, G; Cuccorese, M C; Mano, M P; Bussolati, G
Abstract : Aims —To evaluate which pathological and clinical parameters modify the relation between tumour size and lymph node metastases in invasive breast carcinomas < 20 mm. Methods —In a retrospective study, 1075 patients with pT1 invasive breast carcinoma and with known nodal status were analysed. The size of the infiltrating tumour was microscopically evaluated, and the in situ component was not considered. The additional pathological parameters considered were: tumour grade, peritumoral vascular invasion, multicentricity, and angiogenesis. The immunophenotype of the tumour was determined as: the expression of oestrogen (ER) and progesterone (PR) receptors, p53, and c-erbB2. The patients were grouped by age as follows: < 50, 51–70, and > 70 years old. Results —Three hundred and seventy four patients (34.8%) were node positive. Univariate analysis showed that nodal positivity was significantly correlated with large tumour size (> 10 mm), vascular invasion, grade 2–3, multicentricity, and high angiogenesis (> 100 microvessels/×20 high power frame). No significant correlation was found between nodal positivity and ER, PR, p53, or c-erbB2 status. Interestingly, the association with in situ carcinoma was correlated with lower nodal positivity in tumours presenting equally sized infiltrating components. Age was an independent variable and significantly modified the risk of nodal positivity in tumours < 1 cm. In fact, in patients under 51 years of age, the proportion of nodal positivity in pT1a tumours was sevenfold higher than in older patients. In patients from 51 to 70 years old, nodal positivity correlated with tumour size, and multicentricity was an additional risk factor. Conclusions —These data suggest that, together with tumour size, the presence of in situ carcinoma, and vascular invasion, age is one of the most important predictors of metastatic diffusion in breast carcinomas.